Papua New Guinea - Omot, Norah; Komolong, Birte; Stads, Gert-Jan; Ovah, Raywin; Pham, Nguyen Thi; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2019)
PNG’s agricultural research expenditure declined steadily during 2013–2017 as the combined result of reductions in both donor and government funding. In 2017, PNG invested just 0.31 percent of its AgGDP in agricultural research. In contrast to spending, agricultural researcher numbers rose progressively during 2013–2017 to reach 146 FTEs in total. The country’s research agencies lack the critical mass of highly qualified researchers and accompanying infrastructure needed to address the multidisciplinary challenges facing the agricultural sector. Many critical research areas remain overlooked.